2014
DOI: 10.4236/ojpm.2014.46049
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage Is Elevated in Renal Patients Undergoing Haemodialysis

Abstract: Background: End stage renal disease (ESRD) is associated with an increase in oxidative stress, cardiovascular disease and cancer. The main treatment for ESRD is haemodialysis (HD), which itself induces repetitive bouts of oxidative stress through membrane biocompatibility and endotoxin challenge. The resulting higher levels of reactive oxygen species in turn produce increased levels of oxidative DNA damage leading to genomic instability which may influence the higher risk of cancer reported in HD patients. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…It is a congruence of many vascular diseases with patients having dysfunctions of many physiological pathways. The pathology is in ltrated by other diseases like: diabetes, hypertension [43][44][45], cardiovascular morbidity [46,47] as well as many genetic abnormalities like genomic instability [47,[48][49][50][51]and instability which is later translated into chromosomal damage and ultimately culminating to renal pathologies. Recent progress in genome-wide association studies revealed SNPs linked to different pathologies associated to CKD like: hypertension [52], coronary artery disease [53], subclinical vascular disease [54] and overlapping between genetic variants observed in CKD patients and cardiovascular pathologies [55].…”
Section: Discussionmentioning
confidence: 99%
“…It is a congruence of many vascular diseases with patients having dysfunctions of many physiological pathways. The pathology is in ltrated by other diseases like: diabetes, hypertension [43][44][45], cardiovascular morbidity [46,47] as well as many genetic abnormalities like genomic instability [47,[48][49][50][51]and instability which is later translated into chromosomal damage and ultimately culminating to renal pathologies. Recent progress in genome-wide association studies revealed SNPs linked to different pathologies associated to CKD like: hypertension [52], coronary artery disease [53], subclinical vascular disease [54] and overlapping between genetic variants observed in CKD patients and cardiovascular pathologies [55].…”
Section: Discussionmentioning
confidence: 99%
“…It is a congruence of many vascular diseases with patients having dysfunctions of many physiological pathways. The pathology is in ltrated by other diseases like: diabetes, hypertension [43][44][45], cardiovascular morbidity [46,47] as well as many genetic abnormalities like genomic instability [47,[48][49][50][51]and instability which is later translated into chromosomal damage and ultimately culminating to renal pathologies. Recent progress in genome-wide association studies revealed SNPs linked to different pathologies associated to CKD, like hypertension [52], coronary artery disease [53], subclinical vascular disease [54] and overlapping between genetic variants observed in CKD patients and cardiovascular pathologies [55].…”
Section: Discussionmentioning
confidence: 99%
“…This pathology has a complicated interrelationship with other diseases 2,3 . Diabetes (DM) and hypertension (HT) are the primary risk factors for CKD 4 , and CKD is also associated with cardiovascular morbidity and mortality 5,6 , even in early stages and in young patients 7 .CKD patients are also characterized by a high genomic instability [8][9][10][11] . This instability could be translated to high levels of genetic damage measured by the incidence of chromosomal damage (micronuclei) when their cells are challenged with ionizing radiation 12 and could be either the cause or the consequence of renal pathologies.…”
mentioning
confidence: 99%
“…CKD patients are also characterized by a high genomic instability [8][9][10][11] . This instability could be translated to high levels of genetic damage measured by the incidence of chromosomal damage (micronuclei) when their cells are challenged with ionizing radiation 12 and could be either the cause or the consequence of renal pathologies.…”
mentioning
confidence: 99%